The Efficacy and Safety of Chinese Herbal Medicine Xianling Gubao Capsule Combined With Alendronate in the Treatment of Primary Osteoporosis: A Systematic Review and Meta-Analysis of 20 Randomized Controlled Trials - Chen, Jiaru; Zheng, Junju; Chen, Mangmang; Lin, Shenglei; Lin, Zhou (Frontiers in Pharmacology, 2021)
Objective: Herein, we purposed to evaluate the efficacy along with the safety of Xianling Gubao capsule (XLGB) combined with alendronate (ALE) for primary osteoporosis (POP) from the current literature. Materials and Methods: We carried out a search for electronic literature in the PubMed, Chinese National Knowledge Infrastructure, EMBASE, Wanfang Web of Science, Chinese Biomedical Literature Database, Cochrane Library, as well as Chinese VIP databases targeting articles published from inception to December 2020. Only randomized controlled trials (RCTs) were enrolled into the study. Alkaline phosphatase (ALP), visual analogue scale (VAS), serum phosphorus (S-P), bone gla protein (BGP), serum calcium (S-Ca) and bone mineral density (BMD) were the primary outcome variable. The total clinical effective rate along with the adverse drug reaction (ADR) were the secondary outcome variables. The meta-analysis was conducted using RevMan 5.3 and STATA 12.0. GRADE pro3.6.1 software was used for the assessment of evidence quality. Results: Overall, 20 RCTs focusing on 1911 patients were enrolled into the study. Our meta-analysis demonstrated that XLGB combined with ALE remarkably increased BMD (p < 0.001), BGP (p < 0.001), S-Ca (p < 0.001), S-P (p < 0.001) and effective rate (p < 0.001) than ALE alone in patients with POP. Moreover, ALP (p < 0.001) and VAS (p < 0.001) were overtly by decreased XLGB. However, XLGB combined with ALE would not markedly increase the rate of ADR in contrast with ALE alone (p = 0.499). Conclusion: The results of our study demonstrated that XLGB is a potential candidate for OP treatment. We recommend that rigorous, as well as high-quality trials involving large samples sizes should be conducted to confirm our findings.